2021
DOI: 10.1177/09544089211059320
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of solar parabolic trough receiver using multiple twisted tapes with circular perforation and delta winglet

Abstract: A parabolic trough collector (PTC) is one of the concentrating types of a solar collector working in the medium range of temperature from 100–400 °C, for this reason, the efficiency of the solar parabolic trough is less than other types of concentrating solar collector (Point focusing types) in terms of solar to thermal energy conversion, the improvement in efficiency is achieved by various passive heat augmentation techniques in the receiver tube. One of the promising passive techniques is twisted tape insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The behaviour of this flow structure with multiple longitudinal vortices differs from that of flows in a plain tube. Thapa et al [ 100 ] studied the performance of the parabolic trough receiver by using twisted tape. The author analysed the influence of the twisted tape on the performance of the system.…”
Section: Discussion and Comparative Studymentioning
confidence: 99%
“…The behaviour of this flow structure with multiple longitudinal vortices differs from that of flows in a plain tube. Thapa et al [ 100 ] studied the performance of the parabolic trough receiver by using twisted tape. The author analysed the influence of the twisted tape on the performance of the system.…”
Section: Discussion and Comparative Studymentioning
confidence: 99%
“…They termed it as thermohydraulic performance or thermo-hydraulic performance parameter(THPP). 42 In present study authors conducted detailed literature survey and found that many researchers also developed correlation for heat transfer and friction factor ( ff) which can be used to predict and extrapolate the heat transfer and ff for a wide range of Re. Based on the correlations developed by various researchers, 35,[42][43][44][45][46] author conducted empirical analysis and also calculated thermo-hydraulic performance parameters for these studies.…”
Section: Effect Of Pressure Drop On Thermal Performance Of Spt When U...mentioning
confidence: 99%